When discussion between eyewitnesses helps memory - Vredeveldt, Annelies (Legal and criminological psychology, 2017)
Purpose. Police interviewers are typically instructed to prevent eyewitnesses from talking to each other, because witnesses can contaminate each other's memory. Previous research has not fully examined, however, how discussion between witnesses affects correct and incorrect recall of witnessed events. We conducted quantitative and qualitative analyses to explore the influence of co-witness discussion in more detail. Methods. Witnesses were interviewed individually or in pairs about a videotaped violent event. We conducted individual interviews prior to collaboration (to obtain an independent record of what individuals remembered) and after collaboration (to assess whether collaboration subsequently triggered new memories). Results. Pairs that were interviewed together (collaborative pairs) remembered just as much correct information overall as pairs interviewed individually (nominal pairs), but collaborative pairs made significantly fewer errors. We found evidence of retrieval disruption during the discussion (i.e., collaborative pairs omitted significantly more old information during the second interview than nominal pairs) but also of a delayed cross-cuing effect (i.e., collaborative pairs reported significantly more new information in the final interview than nominal pairs). Pairs who used more content-focused retrieval strategies during the discussion (acknowledgements, repetitions, restatements, and elaborations) reported significantly more information. Conclusions. The current findings suggest that, under certain conditions, discussion between eyewitnesses can help rather than hurt memory. Theoretical and practical implications will be discussed.